2021
DOI: 10.1016/j.clinimag.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging features of coronavirus disease 2019 (COVID-19) pneumonia: The first preliminary case series

Abstract: Rationale and objectives: There is a rising onus on understanding the common features of COVID-19 pneumonia on different imaging modalities. In this study, we aimed to review and depict the common MRI features of COVID-19 pneumonia in our laboratory confirmed case series, the first comprehensive reported cohort in the literature. Materials and methods: Upon IRB approval, eight laboratory confirmed COVID-19 patients who presented to our outpatient imaging clinic underwent chest CT and, once various features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 14 publications
1
46
1
4
Order By: Relevance
“…In a preliminary case series of eight patients, Torkian et al demonstrated visualization of GGOs, consolidation, reticulation, and a reverse halo sign on multiple MRI sequences. 34 T2-weighted turbo spin-echo turbo inversion recovery magnitude (T2W TSE-TIRM) was found to resolve lesions more brightly than the other sequences studied, likely highlighting areas of edema secondary to parenchymal inflammatory changes. Similarly, Ates et al showed no significant differences in MRI detection of GGOs or consolidative lesions versus conventional CT. 33 In their study, MRI had 91.7% sensitivity, 100% specificity, 100% positive predictive value, and 95.2% negative predictive value when using CT as the reference.…”
Section: Mrimentioning
confidence: 95%
See 4 more Smart Citations
“…In a preliminary case series of eight patients, Torkian et al demonstrated visualization of GGOs, consolidation, reticulation, and a reverse halo sign on multiple MRI sequences. 34 T2-weighted turbo spin-echo turbo inversion recovery magnitude (T2W TSE-TIRM) was found to resolve lesions more brightly than the other sequences studied, likely highlighting areas of edema secondary to parenchymal inflammatory changes. Similarly, Ates et al showed no significant differences in MRI detection of GGOs or consolidative lesions versus conventional CT. 33 In their study, MRI had 91.7% sensitivity, 100% specificity, 100% positive predictive value, and 95.2% negative predictive value when using CT as the reference.…”
Section: Mrimentioning
confidence: 95%
“… 5 , 15 , 18 , 25 Bilateral lung involvement most often predominates, usually in a peripheral, subpleural, and posterior distribution. 6 , 7 , 11 , 12 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 Ground-glass opacities (GGOs) – defined as hazy opacities with preservation of the underlying vascular and bronchial architecture 35 – have been most commonly observed, with occurrence rates ranging from 50% to 98% in the adult population 2 , 12 , 14 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 ( Figs. 1 and 2 ).…”
Section: Chest Ctmentioning
confidence: 99%
See 3 more Smart Citations